Fifth Ovarian Cancer Consensus Conference of the Gynecologic Cancer InterGroup: Recommendations on incorporating patient-reported outcomes in clinical trials in epithelial ovarian cancer. (June 2017) - Joly, Florence; Hilpert, Felix; Okamoto, Aikou; Stuart, Gavin; Ochiai, Kasunori; Friedlander, Michael; ,
Abstract: Despite the support for including patient-reported outcomes (PROs) and health-related quality of life in clinical trials, there have been deficiencies in how these have been assessed and reported in epithelial ovarian cancer (EOC) clinical trials. To redress this, the 5th Ovarian Cancer Consensus Conference, included a plenary session entitled 'How to include PROs in clinical trials'. The perspective is a summary of the recommendations made by the Gynecologic Cancer InterGroup unanimously agreed on the importance of PROs and PRO end-points in EOC clinical trials. They recognised that effort must be made to ensure the integrity of collection of PRO data and to avoid missing data. PRO end-points should be based on the PRO hypotheses, be context specific and reflect the patient population and the objectives of treatment (e.g. first line, maintenance therapy, early or late relapse). The PRO end-points inform the choice of PRO measures used in the trial and how the results are analysed and reported. There was agreement that progression-free survival should be supported by PROs among patients with late relapse (platinum sensitive) and that progression-free survival alone was not sufficient as the primary end-point of clinical trials in patients with platinum resistant/refractory EOC and PROs should be included as either the primary/co-primary end-point in this subset of patients. Novel approaches to measure the benefit of palliative chemotherapy such as time until definitive deterioration of Health-Related Quality of Life were recommended. There was consensus to endorse the ISOQOL and CONSORT-PRO guidelines on the inclusion and reporting of PRO endpoints in protocols and that all future EOC Gynecologic Cancer InterGroup trials should adhere to these. Highlights: Patients-reported outcomes (PROs) end-points should be included in epithelial ovarian cancer clinical trials. Effort must be made to ensure the integrity of collection of PRO data and to avoid missing data. PRO end-points should be based on the PRO hypotheses. PRO end-points should be context specific, reflect the patient population and the objectives of treatment (first line, maintenance therapy, early or late relapse). Progression-free survival should be associated with PROs when it is the primary end-point of clinical trials in patients with resistant/refractory epithelial ovarian cancer.